Interface psicologia e aconselhamento pastoral: o cuidado nas crises atrávés da psicologia pastoral - Rosa, Alexandre (2012)
This work inquires on the interface of the psychological science with pastoral advising culminating in the contributions of the psychology pastoral. The first chapter covers the development of psychology and addresses some contemporary to traditional schools. The second chapter glimpses the history of pastoral counseling and its evolution, elapsing by prominent models, such as Jay Adams fundamentalism, the model as evangelical Gary Collinsand finally the holistic model of liberation and growth of Howard Clinebell, beyond its highlight to the healing ministry as broad and inclusive of the entire Christian community. It points out the ministry of pastoral counseling as great evidence today. The pastoral psychology is presented in the third chapter as point of confluence of the psychology and of pastoral advising, so at the same time in what it uses the science it is also it is an ecclesiastical ministry. The backdrop to this study exposes the postmodern and the moment of social transition, the possible contemporary crises and the role of pastoral counseling in different situations. Pastoral counseling is a time and advised counsel that go together, reflecting the situations experienced in order to empower the individual to make autonomous choices weakened and resume the course of your life.